Studies on colostrum minerals and their transfer to suckling calves in buffaloes - Sikka, P; Lal, D; Khanna, S; Tomer, A K S; Sethi, R K (The Indian Journal of Animal Sciences, 2011)
Advance pregnant buffaloes (30) of fourth - sixth parity, average body weight of 550 ± 15 kg, were randomly selected and fed 25 kg green, 2-3 kg straw and 3-4 kg concentrate mixture per animal/day. Vitamin AD3E triplex (fat soluble/antioxidant vitamins) was injected i/m, twice at 15 days interval to 15 animals 1 month prior to expected calving date. Rest of the animals were kept as negative controls. Minerals and immunoglobulins (Ig) were estimated in colostrum and blood of respective calves to study the impact of antioxidant vitamins on secretion of minerals and Ig in colostrum and transfer of essential nutrients as minerals and Ig from colostrums to newly born calves during passive transfer of nutrients. Antioxidant vitamins injections enhanced the secretion of calcium and 19 during the first 3 days, however, enhancement in copper and zinc was seen on first day. It indicates an interaction among fat soluble vitamins and minerals in adult buffaloes; their transfer frol11 colostrul11s to calves and likely impact of fat soluble vitamins on mineral absorption in calves. The variation in the levels of colostral minerals are projected in caffserum during first few Jays when calves arc dependent on suckling for nutrients predominantly. Serum zinc, copper and magnesium levels showed notable variation in calves born to vitamins supplemented dams.